2019
DOI: 10.1097/olq.0000000000000917
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia, Gonorrhea, and Human Immunodeficiency Virus Infection Among Transgender Women and Transgender Men Attending Clinics that Provide Sexually Transmitted Disease Services in Six US Cities: Results From the Sexually Transmitted Disease Surveillance Network

Abstract: Background Transgender women and transgender men are disproportionately affected by human immunodeficiency virus (HIV) infection and may be vulnerable to other sexually transmitted diseases (STDs), but the lack of surveillance data inclusive of gender identity hinders prevention and intervention strategies. Methods We analyzed data from 506 transgender women (1045 total visits) and 120 transgender men (209 total visits) who attended 26 publicly funded c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 25 publications
2
44
1
Order By: Relevance
“…San Francisco, CA, was a primary study site in seven of the nine U.S. studies, with New York City, NY, and Boston, MA, also being represented in four and two studies, respectively. 11,30,31,37,38,41,45,49,50 Only one multisite study presented data from the Southeastern United States, with a study site in Atlanta, GA. 31 The non-U.S. studies included a variety of global regions, and while the majority revolved around urban areas, only one study from Argentina intentionally performed analyses on both urban and rural populations. 47 All 25 studies reported data on transgender women, with only 9 (36%) reporting data on transgender men.…”
Section: Resultsmentioning
confidence: 99%
“…San Francisco, CA, was a primary study site in seven of the nine U.S. studies, with New York City, NY, and Boston, MA, also being represented in four and two studies, respectively. 11,30,31,37,38,41,45,49,50 Only one multisite study presented data from the Southeastern United States, with a study site in Atlanta, GA. 31 The non-U.S. studies included a variety of global regions, and while the majority revolved around urban areas, only one study from Argentina intentionally performed analyses on both urban and rural populations. 47 All 25 studies reported data on transgender women, with only 9 (36%) reporting data on transgender men.…”
Section: Resultsmentioning
confidence: 99%
“…Among 105 transgender men attending STI clinics, urogenital positivity was 7.1%, pharyngeal positivity was 5.9% and rectal positivity was 14.7%. 74 Comparable positivity was found among other samples from San Francisco, California, USA and Melbourne, Australia. 73,78 In contrast, none of the 82 transgender male youth attending a community health clinic in Boston, Massachusetts, USA, had gonorrhoea.…”
Section: Transgender Personsmentioning
confidence: 86%
“…Whereas the gonorrhoea positivity of urogenital specimens ranged from 0.1% (among 764 women from drop-in centres in Thailand) to 2.8% (among 406 STI clinic attendees at multiple sites in the USA), positivity of pharyngeal specimens ranged from 3.5 to 37.3% across studies (with positivity of 8.1-9.8% in the two largest studies from Thailand and the USA). [72][73][74][75] Positivity among rectal specimens ranged from 6.3 to 43% (9.6-11.8% in the Thailand and USA studies). [72][73][74][75][76] Two studies that did not mention the anatomic site of specimen collection found a prevalence among transgender women of 2.1% (among 63 young adults in the USA) and 4% (among 77 STI clinic attendees in Australia).…”
Section: Transgender Personsmentioning
confidence: 96%
See 1 more Smart Citation
“…56,57 This is especially important for people of transgender experience given their elevated HIV risk. 58 Counseling about risk reduction includes discussions about HIV pre-exposure prophylaxis (PrEP) and postexposure prophylaxis. Studies indicate that knowledge about PrEP is low among transgender women.…”
Section: Hivmentioning
confidence: 99%